2011
DOI: 10.1016/j.juro.2010.12.059
|View full text |Cite
|
Sign up to set email alerts
|

A Contemporary Analysis of Outcomes of Adenocarcinoma of the Prostate With Seminal Vesicle Invasion (pT3b) After Radical Prostatectomy

Abstract: Purpose Despite earlier detection and stage migration, seminal vesicle invasion is still reported in the prostate specific antigen era and remains a poor prognostic indicator. We investigated outcomes in men with pT3b disease in the contemporary era. Materials and Methods The institutional radical prostatectomy database (1982 to 2010) of 18,505 men was queried and 989 with pT3b tumors were identified. The cohort was split into pre-prostate specific antigen (1982 to 1992), and early (1993 to 2000) and contemp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
63
4
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 30 publications
8
63
4
1
Order By: Relevance
“…Despite the high rate of BCR in patients with pT3b disease, cancerspecific survival was excellent in our small series, and this favorable outcome was also confirmed by other previous reports (4)(5)(6)(7)(8). Although post-operative management has not been clearly defined for pT3b cases (5,10,11), multimodal treatments including radiation to the prostatic bed or hormonal therapy will allow the patients to survive for many years even after PCa growth beyond the gland.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Despite the high rate of BCR in patients with pT3b disease, cancerspecific survival was excellent in our small series, and this favorable outcome was also confirmed by other previous reports (4)(5)(6)(7)(8). Although post-operative management has not been clearly defined for pT3b cases (5,10,11), multimodal treatments including radiation to the prostatic bed or hormonal therapy will allow the patients to survive for many years even after PCa growth beyond the gland.…”
Section: Discussionsupporting
confidence: 86%
“…Considering prognostic factors for BCR of pT3b patients, Gleason score of surgically removed whole-mount sections, surgical margin status, pre-operative PSA and clinical stage have been considered as independent predictors (4,5,7,8). In this investigation, we only selected four variables considering our small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] While the incidence of SVI has decreased of late, the survival rate of men with SVI has not changed significantly. 1 Eggener et al reported that the respective 4-and 7-year cancer-specific survival rates were 95% and 80% in men with SVI in the pre-PSA era compared with 99% and 93%, in the PSA era (P = 0.02). 2 However, a recent large study failed to show any improvement in survival.…”
Section: Discussionmentioning
confidence: 99%
“…The most common variables are Gleason score, clinical T-stage and presence of positive surgical margins [1,13,14,15,33]. MRI provides detailed anatomical information that can be used for surgical planning or application of radiotherapy or further risk stratification [34].…”
Section: Discussionmentioning
confidence: 99%
“…Invasion of the seminal vesicles (SVI) in patients with prostate cancer (PCa) is reported after radical prostatectomy in 3.3-7.7% of the cases [1]. Those patients with pT3b disease exhibit a poorer prognosis due to increased treatment failure and tumor recurrence [2].…”
Section: Introductionmentioning
confidence: 99%